Multifunctional Materials: A Case Study of the Effects of Metal Doping on ZnO Tetrapods with Bismuth and Tin Oxides. (30th December 2016) - Postica, Vasile; Gröttrup, Jorit; Adelung, Rainer; Lupan, Oleg; Mishra, Abhishek Kumar; de Leeuw, Nora H.; Ababii, Nicolai; Carreira, José F. C.; Rodrigues, Joana; Sedrine, Nebiha Ben; Correia, Maria Rosário; Monteiro, Teresa; et al.
Abstract : Hybrid metal oxide nano‐ and microstructures exhibit novel properties, which make them promising candidates for a wide range of applications, including gas sensing. In this work, the characteristics of the hybrid ZnO‐Bi2 O3 and ZnO‐Zn2 SnO4 tetrapod (T) networks are investigated in detail. The gas sensing studies reveal improved performance of the hybrid networks compared to pure ZnO‐T networks. For the ZnO‐T‐Bi2 O3 networks, an enhancement in H2 gas response is obtained, although the observed p‐type sensing behavior is attributed to the formed junctions between the arms of ZnO‐T covered with Bi2 O3 and the modulation of the regions where holes accumulate under exposure to H2 gas. In ZnO‐T‐Zn2 SnO4 networks, a change in selectivity to CO gas with high response is noted. The devices based on individual ZnO‐T‐Bi2 O3 and ZnO‐T‐Zn2 SnO4 structures showed an enhanced H2 gas response, which is explained on the basis of interactions (electronic sensitization) between the ZnO‐T arm and Bi2 O3 shell layer and single Schottky contact structure, respectively. Density functional theory‐based calculations provide mechanistic insights into the interaction of H2 and CO gas molecules with Bi‐ and Sn‐doped ZnO(0001) surfaces, revealing changes in the Fermi energies, as well as charge transfer between the molecules and surface species, which facilitate gas sensing. Abstract : Gas sensing and optical properties of hybrid 3D ZnO‐T (tetrapods) with Bi2 O3 and Zn2 SnO4 networks are reported. The investigations reveal improved gas sensing performances of hybrid networks compared with pure ZnO‐T (tetrapod) networks. The described synthesis strategy serves as an excellent method to fabricate enhanced and selective gas sensors. ZnO‐T‐Bi2 O3 hybrids enhance H2 gas response whereas ZnO‐T‐Zn2 SnO4 changes selectivity to CO.